Performance Analysis of Alkaline Fuel Cell with Variation of Potassium Hydroxide Concentration in Electrolyte Solution - Alfariz, Mohammad Rifqy; Ilminnafik, Nasrul; Djumhariyanto, Dwi; Hardiatama, Intan; Ibnu, Muhammad Khadafi; Nugraha, Raafi Aditya; Freitas, Domingos de Sousa (Universitas Negeri Malang, 2025)
Alkaline Fuel Cell (AFC) is a green energy conversion tool that converts chemical energy into electrical energy through electrochemical reactions. This research aims to analyze the effect of potassium hydroxide (KOH) concentration variation in electrolyte solution on the AFC performance, using nickel and manganese catalysts. The research methods include experiments using various KOH concentrations to determine the optimal concentration to produce the best AFC performance. The voltage and current produced are measured, as well as the calculation of the electrical power and efficiency of the AFC. The results showed that KOH concentration has a significant influence on the performance of AFC. It was found that the optimal KOH concentration produces maximum electrical power and energy conversion efficiency. The highest alkaline fuel cell performance was found at 70% KOH concentration. In addition, the use of nickel and manganese catalysts was shown to improve the stability and efficiency of AFC. The result makes an important contribution to the development of AFC technology, supporting global efforts towards cleaner and more sustainable energy use. The findings also provide a basis for further innovations in AFC design and materials, as well as their potential in practical applications such as electric vehicles and portable power plants